Musculoskeletal loading and implications for injury - Derrick, T. R. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
There are numerous variables used to assess musculoskeletal loading during human movement. This presentation will examine ground reaction forces, segment accelerations, joint contact forces and internal bone stresses and strains. I will cover implications for injury assessment, subtleties of interpretation, benefits and drawbacks of each these methods.